2022
DOI: 10.2147/dmso.s349528
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Hub Genes in Acute Pancreatitis and Hypertriglyceridemia

Abstract: Background The pathogenesis of acute pancreatitis (AP) and the relationship between acute pancreatitis and hypertriglyceridemia are complex and not fully understood. The purpose of this study was to identify the hub genes along with common differentially expressed genes (DEGs) between acute pancreatitis and hypertriglyceridemia. Methods We downloaded three gene expression profiles of AP and one gene expression profile of hypertriglyceridemia from the Gene Expression Omn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The study of [ 48 ] emphasizes that high inflammatory cytokines might induce the accumulation of unfolded or misfolded proteins, i.e., endoplasmic reticulum stress in diabetic pancreatic islets. In the CC category functional enrichment investigation, Zhang et al, 2022 [ 49 ] discovered that the upregulated differentially expressed genes concerning acute pancreatitis were connected with the cell–substrate junction. On the other hand, chaperones’ adaptive unfolded protein response signaling maintained endoplasmic reticulum protein folding equilibrium in healthy beta cells, according to Yong et al, 2021 [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study of [ 48 ] emphasizes that high inflammatory cytokines might induce the accumulation of unfolded or misfolded proteins, i.e., endoplasmic reticulum stress in diabetic pancreatic islets. In the CC category functional enrichment investigation, Zhang et al, 2022 [ 49 ] discovered that the upregulated differentially expressed genes concerning acute pancreatitis were connected with the cell–substrate junction. On the other hand, chaperones’ adaptive unfolded protein response signaling maintained endoplasmic reticulum protein folding equilibrium in healthy beta cells, according to Yong et al, 2021 [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al suggested that AP and hypertriglyceridemia shared common DEGs, WSB1 and FBXO4 (8). Therefore, different studies reported different hub DEGs for AP, which might be due to implementation of different bioinformatic analysis methods (5)(6)(7)(8). In addition, these studies did not evaluate test hub genes as predictive factors of SAP.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of bioinformatics approaches is aiding in gaining a deeper understanding of disease pathobiology at the genetic level and in the development of predictive genetic biomarkers. Numerous studies have explored potential hub differentially expressed genes (DEGs) for acute pancreatitis through bioinformatics analysis (5)(6)(7)(8). Fan et al have suggested that genes EGFR, CDH1, ACTB, CD44, and VCL may play vital role in the pathogenesis of AP (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatic analysis of high-throughput sequencing data plays an important role in medical research. In fact, there are some studies based on bioinformatic analysis in AP (15)(16)(17)(18). However, all of these analyses are based on the identification of differentially expressed genes (DEGs), and this method could result in the omission of large-scale information from unrecognized genes.…”
Section: Introductionmentioning
confidence: 99%